Kaliningrad Oblast 2024: Russia's vessel of havoc on the Baltic Sea - Miłosz J. Cordes (Danish Institute for International Studies (DIIS), 2024)
Kaliningrad Oblast was created as a war trophy and a symbol of Soviet victory over Nazi Germany in 1945/1946. For nearly seven decades, it played a strictly military role in Soviet and Russian foreign policy, mostly limited to its Baltic Sea surroundings. This changed when Vladimir Putin came back to the Kremlin for his third presidential term. With the annexation of Crimea, followed by Russia's invasion of Ukraine, the semi-exclave's visibility and importance in other geographical and topical areas increased significantly. It has become an inherent part of the so-called neoconservative project pursued by the Russian federal authorities. In this optic, Russia wages a defensive war against the West and its decadent values, pulling all of its resources together and preparing for a long-term confrontation. Kaliningrad Oblast, with seven centuries of non-Russian history, has become a showcase of this approach. It has also been put in the spotlight of this existential conflict as one of the most vulnerable regions, separated from mainland Russia by EU and NATO countries, entailing negative consequences. This report provides an overview of the situation in the Oblast as of early 2024 in five key dimensions: (1) politics, economy and demographics; (2) the Russian neo-imperial narrative; (3) international environment; (4) Russia's invasion of Ukraine of 24 February 2022; (5) security developments in the Baltic Sea region with an impact on the dynamics of EU-Russia and NATO-Russia relations, and on Denmark.
Keywords: 300; Kaliningrad Oblast; Russia; Russian Federation; NATO; EU; Baltic Sea Region; Denmark; Poland; Lithuania; Ukraine